Difficulty in moving around in a wheelchair as a presenting symptom of left atrial myxoma in a chronic paraplegic patient: A case report - Kovindha A. (Nature Publishing Group, 2014)
Study design:Case report.Objectives:To present and discuss a case of a chronic paraplegic patient who presented with difficulty in moving around in a wheelchair.Setting:Rehabilitation Ward, Maharaj Hospital, Faculty of Medicine, Chiang Mai University, Thailand.Case report:A chronic complete paraplegic T4 man complained of difficulty in moving around in a wheelchair. He had experienced this difficulty for a week. He also complained of pain in the finger pads, and blackening had occurred in his little toes. Buerger's disease was suspected, but Doppler ultrasound showed no evidence of arterial occlusion. During admission, his vision suddenly dropped and magnetic resonance imaging revealed an ischemic stroke in the posterior cerebral artery. Erythematous lesions in all toe pads and soles were actually embolic signs but painless due to his paraplegia. Echocardiography showed a large left atrial myxoma. Six weeks after removal of the left atrial myxoma, he was discharged when he could propel his wheelchair more than 100 m without difficulty or pain.Conclusion:Experiencing difficulty in moving around in a wheelchair in conjunction with painful finger pads can be presenting symptoms of a rare cardiac lesion - left atrial myxoma with arterial embolism. After surgical excision of the tumour, the arterial embolic symptoms and signs subsided and the patient regained basic wheelchair mobility skills within 6 weeks. © 2014 International Spinal Cord Society All rights reserved.